Properties of the ZrO2MgO/MgZrO3NiCr/NiCr triple-layer thermal barrier coating deposited by the atmospheric plasma spray process - Mrdak, Mihailo Rade (Vojnotehnički glasnik / Military Technical Courier, 2015)
This paper presents the results of the examinations of TBC - ZrO2MgO / MgZrO3NiCr / NiCr thermal barrier layers deposited by the plasma spray process at the atmospheric pressure on substrates of Al alloys. In order to obtain the structural and mechanical properties of layers, which will provide a good heat and abrasion protection of the tail elevators of aircraft J-22 when firing "Lightning" and "Thunder" rockets, the deposition of three powder types was performed on 0.6 mm thick Al alloy substrates. This study describes a procedure of using triple-layer TBC coatings as a good combination among many available ones, which gives a good compromise between thermal protection and resistance to abrasion for protecting aircraft tail elevators. The study is mainly based on the experimental approach. The evaluation of the mechanical properties of layers was done by the examination of microhardness by method HV0.3 and bond strength on the tensile machine. The structure of layers was examined by the method of light microscopy while the surface of ZrO2MgO ceramic layers was examined by the method of scanning electron microscopy (SEM).The thermal protection of TBC layers and resistance to abrasion were tested in the tunnel of the MilitaryTechnical Institute, Zarkovo. The obtained characteristics of the surface layers and the rocket firing simulations have proven the triple-layer system of TBC coatings reliable.